THE USE OF GRAMMARLY TO ENHANCE STUDENTS' ACCURACY IN WRITING DESCRIPTIVE TEXT - Aprilia Wismatul Fauziah Hadiat (Journal of English Education Program (JEEP), 2022)
The purpose of the study is to find out the use of Grammarly to enhance students’ skill in writing descriptive text and to figure out the students’ perceptions on the implementation of Grammarly to enhance the accuracy of writing descriptive text. This case study involves 30 students at class VIII as research participants. The data of this study are gathered from the questionnaire, the interview, and the online classroom observation. The data analysis uses four techniques including the frequency table, content analysis, coding, and triangulation analysis. The findings reveals that the use of Grammarly can enhance the accuracy of writing descriptive text. The findings also shows that most of students give positive perceptions towards the use of Grammarly in writing descriptive text because it can make the students motivated to enhance their writing skill, makes it easy for them to find out the mistakes in writing a text, avoid plagiarism, more thoroughly when there are writing errors, and they are more confident when writing a text using Grammarly.  Finally, future researchers are expected to conduct the research quantitatively with similar topic to enrich this study.